PENERAPAN ANALISIS KONJOIN UNTUK MENENTUKAN PREFERENSI MASYARAKAT KOTA PADANG TERHADAP PENGGUNAAN JASA OJEK ONLINE TAHUN 2019 - Suci Wulandari; Fitri Mudia Sari (Jurnal Statistika Universitas Muhammadiyah Semarang, 2019)
Transportation services in Indonesia continue to experience developments in the field of technology. This is indicated by the emergence of application-based online transportation. One of the most common types of online transportation is online motorcycle taxi. The number of online motorcycle taxi brands with a variety of products and facilities offered, has caused problems for online motorcycle taxi entrepreneurs.Therefore, a study is needed to find out what are the preferences of consumers in using online motorcycle taxi services. One method that can explain consumer preferences is the conjoined method. The data used is in the form of metric data with rating evaluations on the combination of levels of each attribute. Based on the results of the study, obtained the highest utility value for the price attribute is a special promo price of19.9375, a method of cash payment of 6.8125, friendly driver service at 88.5625, and drivers using uniform at 39.6875. The most preferred combination is a special promo price, cash, friendly, and the driver uses the uniform. While the least preferred combination is the normal price, non-cash, not friendly, and drivers do not use uniforms. Then the most important attribute for the community is the driver service attribute. Keywords: Conjoint Analysis, Online Motorcycle Taxi, Preferences, Rating